Citizen journalism vs. traditional journalism : a case for collaboration - Barnes, Corinne (2012)
Suggests that there is a place for the emerging phenomenon called citizen journalism, i.e. the act of a citizen or group of citizens involved in the process of collecting, reporting, analysing and disseminating news and other forms of information; alongside that of the profession that has been practised for decades called mainstream or traditional journalism.